Carcinoma Ex-Pleomorphic Adenoma of the Lacrimal Gland with Intracranial Extension - Sharbel, Daniel; Atekha, Osayamen; Rahimi, Scott; Byrd, James Kenneth (Journal of Neurological Surgery Reports, 2025)
Carcinoma ex-pleomorphic adenoma (CXPA) of the lacrimal gland is rare, and its management can be complex given its anatomic location. In this case report, we describe our approach to multidisciplinary management of a CXPA with intracranial extension.
Keywords: carcinoma ex-pleomorphic adenoma; lacrimal gland; skull base; free flap